2022
DOI: 10.3390/nano12132296
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Characterization of Silver Nanoparticles with High Antibacterial Activity Using Cell Extracts of Cyanobacterium Pseudanabaena/Limnothrix sp.

Abstract: In this work, we demonstrated the ability of the cyanobacterium Pseudanabaena/Limnothrix sp. to produce ultra-small silver nanoparticlesin the forms of metallic silver (Ag0) and silver oxides (AgxOy) via a facile green synthetic process. The biological compounds in the cyanobacterial cellular extract acted both as reducing agents for silver ions and functional stabilizing agents for the silver nanoparticles. Furthermore, the antibacterical activity of the as-synthesized nanoparticles against Gram-negative Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Silver nanoparticles' geometric mean diameter and geometric standard deviation, respectively, ranged from 6.2-21.5 nm and 1.23-1.88 nm. Recent research has shown that the polyol method yields spherical nanoparticles of various sizes when laser ablation is used [29,30]. Silver nanoparticles were created using laser ablation using various wavelengths to explore the effects of the wavelength on particle size.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Silver nanoparticles' geometric mean diameter and geometric standard deviation, respectively, ranged from 6.2-21.5 nm and 1.23-1.88 nm. Recent research has shown that the polyol method yields spherical nanoparticles of various sizes when laser ablation is used [29,30]. Silver nanoparticles were created using laser ablation using various wavelengths to explore the effects of the wavelength on particle size.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs), a broad-spectrum bactericide, had strong bactericidal effects on fungi and viruses. 21 , 22 AgNPs possessed high affinity with microorganisms due to the electrostatic attraction between the negative charge of the bacteria membrane and the positive charge of the AgNPs. After subsequent penetration, AgNPs locally release Ag + ions to induce antibacterial effects in bacterial death.…”
Section: Introductionmentioning
confidence: 99%
“…They play an important role in agriculture, where they are used as crop protection agents, and in medicine, where they have an antimicrobial function [ 5 , 6 , 7 ]. Among the variety of nanomaterials, silver nanoparticles (AgNPs) belong to the group that is most intensively studied and used, mainly due to their high reactivity resulting from a large surface-to-volume ratio, leading to strong biocompatibility and antibacterial and antiviral properties [ 8 , 9 , 10 , 11 , 12 ]. Due to their numerous beneficial applications, AgNPs are increasingly incorporated into many commercially available products, leading to concerns about their uncontrolled release into the aquatic environment and potentially harmful effects on the ecosystem and human health [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%